PENGARUH PEMBERIAN KEONG SAWAH DAN AIR CUCIAN BERAS TERHADAP PERTUMBUHAN BELUT (Monopterus albus Zuieuw) - Irham Falahudin; delima engga mareta; rika yera puspa (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2016)
Snail and rice water has a very high protein content so the snail meat and rice water can be used as an additional food that is good for eel. Giving snail and rice water as a feed supplement in the eel (Monopterus albus) is expected to boost growth in the eel. This study aimed to determine the effect of snails and rice water on the growth of eel (Monopterus albus) and know Where feed to get optimal results on the growth of eel (Monopterus albus). Research conducted at the Laboratory of MIPA IAIN Raden Fatah Palembang. This study used a Rancangan Acak Lengkap (RAL) with 4 treatments and 6 replications. Such treatment is A : pellets 4.5 grams, B : 150 ml of rice water + 3 grams of snail, C : 100 ml rice water + 3.5 grams of snail, D : 50 ml rice water + 4 grams of snail. The analysis showed that the highest growth in treatment D is 50 ml rice water + 4 grams of snail. The conclusion is giving snail and rice water in the eel (Monopterus albus) significant effect on the growth of the body's weight and length of the eel.